Transforming growth factor-β1 induces desmoplasia in an experimental model of human pancreatic carcinoma1 - Löhr, J.-Matthias; Schmidt, Christian; Ringel, Jörg; Kluth, Mario; Müller, Petra; Nizze, Horst; Jesenofsky, Ralf (Cancer research, 2001)
Proliferation of fibrotic tissue (desmoplasia) is one of the hallmarks of several epithelial tumors including pancreatic adenocarcinoma. This tissue reaction may be deleterious or advantageous to the host or tumor. In a systematic analysis, we identified two growth factors expressed by human pancreatic carcinoma cells that are positively correlated with the ability to induce fibroblast proliferation both in vitro and in vivo, i.e., transforming growth factor (TGF)-β1 and fibroblast growth factor-2. Here we demonstrate that the overexpression of TGF-β1 induced up-regulation of matrix proteins and growth factors in the TGFβ1-transfected pancreatic tumor cells. Furthermore,transfection of PANC-1 cells induces the same change in fibroblasts in either cocultivation experiments or when they are grown in conditioned medium from TGF-β1-transfected PANC-1 cells. TGF-β1-transfected pancreatic tumor cells induced a rich stroma after orthotopical transplantation in the nude mouse pancreas. The transfer of a single growth factor, TGF-β1, conveys the ability to induce a fibroblast response similar to that seen in desmoplasia in human pancreatic adenocarcinoma. This effect cannot only be attributed to direct effects of TGF-β1 but also results from the up-regulation of several other factors including collagen type I, connective tissue growth factor, and platelet-derived growth factor.
Gesehen am 24.05.2022